A Drop in Number of Hospitalizations Among Children with Bacterial Infections During the COVID-19 Pandemic. Issue 1 (January 2021) - Gavish, Rachel; Krause, Irit; Goldberg, Lotem; Bilavsky, Efraim; Kadmon, Gili; Livni, Gilat; Scheuerman, Oded; Levinsky, Yoel
Abstract : A significant drop was found in the number of hospitalizations due to bacterial infections among children during the first peak period of COVID-19 in Israel. There was a 77% decrease in serious bacterial infections, and ≥50% decrease in most types of bacterial infections, especially osteoarticular and skin infections, followed by pneumonia and ENT infections.